Intermolecular structure and hydrogen-bonding in liquid 1, 2-propylene carbonate and 1, 2-glycerol carbonate determined by neutron scattering. Issue 4 (10th January 2017) - Delavoux, Yoan M.; Gilmore, Mark; Atkins, Martin P.; Swadźba-Kwaśny, Małgorzata; Holbrey, John D.
Abstract : Propylene carbonate CO⋯H–C hydrogen-bonding motifs are disrupted in glycerol carbonate by the presence of the hydroxyl group. Abstract : Neutron diffraction with isotopic substitution has been used to investigate the liquid structures of propylene carbonate and glycerol carbonate. C–H⋯OC hydrogen-bonding motifs dominate the local structure of propylene carbonate, giving rise to the formation of head-to-tail correlated chains of molecules. In contrast, glycerol carbonate exhibits a more disordered structure with no overall dominant interactions in which the pendant hydroxyl function disrupts structure-making correlations present in propylene carbonate.